Falun Dafa truthfulness, compassion, forbearance. (Falun Dafa, 2002)
Falun Dafa or Falun Gong is a holistic cultivation system that is based on the characteristics of the universe: truthfulness, compassion and forbearance. It is a popular qigong activity and does not have any particular organizational structure, nor any political objective.